2015
DOI: 10.1049/iet-smt.2014.0194
|View full text |Cite
|
Sign up to set email alerts
|

Correlation matrices in kriging assisted optimisation of electromagnetic devices

Abstract: Kriging surrogate modelling facilitates efficient decision making regarding where to place the next point for evaluation during optimisation. This is particularly helpful in the design of electromagnetic devices where computationally expensive numerical field modelling needs to be used. The disadvantage, however, is that correlation matrices are required which, for problems with many design variables and multiple objectives, may grow in size leading to the need for page swapping and thus slowing down of what i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Notwithstanding, it should be noted that when using a computer with limited memory there will be difficulties associated with running the numerical simulation software too, which the Kriging model is trying to replace, so the issues of limited available memory are not unique to Kriging formulation; they must, however, be addressed. One possible way forward for much larger practical problems with many variables is to explore the sensitivity of the objective function to changes in all parameters and focus on a subset of such parameters; this idea is pursued in the follow-up work [23].…”
Section: Three-parameter Test Resultsmentioning
confidence: 99%
“…Notwithstanding, it should be noted that when using a computer with limited memory there will be difficulties associated with running the numerical simulation software too, which the Kriging model is trying to replace, so the issues of limited available memory are not unique to Kriging formulation; they must, however, be addressed. One possible way forward for much larger practical problems with many variables is to explore the sensitivity of the objective function to changes in all parameters and focus on a subset of such parameters; this idea is pursued in the follow-up work [23].…”
Section: Three-parameter Test Resultsmentioning
confidence: 99%
“…However, a theoretically optimum solution may not be the most robust or stable [49]. Fabrication tolerances and deviations can adversely affect the device performance and thus a pareto front solution, that may not have the best performance but is more stable with parameter uncertainty, may hold the key to physically viable implementations [50]. These techniques have been explored in the context of antenna and antenna arrays as well as micro-/sub-millimeter wave components.…”
Section: Theoretical Methods To Design Em Media/devicesmentioning
confidence: 99%
“…However, it was found that large-scale tasks-multi-objective and employing many design variables-may lead to a "combinatorial explosion" when all the required correlation matrices are established between the sample points and the design vectors. The partitioning scheme [4] of the correlation matrices, splitting them into manageable sizes, can mitigate to some extent the burden of storing this massive amount of data, but sacrifices may need to be made in terms of computing efficiency at each iteration to achieve more available physical memory. Therefore, a more efficient method capable of removing this bottleneck is sought.…”
Section: Introductionmentioning
confidence: 99%